1937
DOI: 10.1002/aja.1000600204
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the suprarenal glands of dogs. I. Comparison of the weights of suprarenal glands of mature and immature male and female dogs

Abstract: There is much evidence that points toward an intimate relationship between the suprarenal glands aiid the various phases of reproduction iii rodents but such a relatioriship has not been reported for dogs. There are reports of changes in the weights of the suprarenals with relation to sex and phases of the oestrous cycle in rats, guinea pigs, rabbits, pigeons, cats and moles.Elliott arid Tuckett ('06) noted that the suprarenals of the rat, cat, guinea pig and rabbit develop equally in each sex until the time o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1
2

Year Published

1940
1940
1972
1972

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 7 publications
0
8
1
2
Order By: Relevance
“…Hatai, 1914;Baker, 1937) and in mice (Chester Jones, 1948Jones, , 1955. However, it is interesting to note that the magnitude of the sex difference was strain-dependent.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…Hatai, 1914;Baker, 1937) and in mice (Chester Jones, 1948Jones, , 1955. However, it is interesting to note that the magnitude of the sex difference was strain-dependent.…”
Section: Discussionmentioning
confidence: 43%
“…Sexual dimorphism of the adrenal weights was first noted by Hatai (1914) in rats. Baker (1937) found similar sex differences in guinea-pigs and subsequent studies on other mammals have shown that sexual dimorphism in adrenal weight is common.…”
Section: Introductionmentioning
confidence: 46%
“…The macroscopic anatomy of the dog adrenal including the general morphology, embryology, blood supply, venous drainage and innervation has been reviewed previously (Flint, 1900;Baker, 1937;Stockard, 1941;Randolph, 1950;Bachmann,1954;St. Clair, 1957;Smithcors, 1964;Haensly and Getty, 1965;Hullinger, 1966).…”
Section: Dog (Canine Familiaris) Adrenal Morphologymentioning
confidence: 42%
“…De acordo com Baker (1936), Venzke (1975), Hullinger (1979), Yeh (1980), Getty (1986), Waters (1993, Green (1996) e Dyce, Sack e Wensing (2004), as glândulas adrenais têm comprimento de 2 a 3 centímetros; a largura é de 1 centímetro; e a altura, de meio centímetro.…”
Section: Adrenalunclassified